Innovative hierarchical V4O7/V2O5/Zn2V2O7 Microflowers: High-performance photocatalysts for methylene blue elimination - Ashish Somwanshi; Kriti Kumari; Satyapal S Rathore; Rashi Nathawat (Materials Research Express)
Photocatalytic materials with enhanced charge separation and sunlight-driven degradation of organic dye are crucial for advancement in wastewater treatment solutions. In the present investigation, three-phase nanocomposites V _4 O _7 / V _2 O _5 / Zn _2 V _2 O _7 , exhibiting excellent photocatalytic performance under natural sunlight, were synthesized using a microwave-assisted method and characterized through x-ray Diffraction (XRD), Field Emission Scanning Electron Microscopy (FESEM), UV-Visible Spectroscopy (UV–vis), and Photoluminescence (PL) techniques. XRD confirmed the phase composition of V _4 O _7 , V _2 O _5 , and Zn _2 V _2 O _7 , with no detectable impurity phases. Additionally, electron images showed that all the mixtures formed round clusters that were very porous and looked like tiny flowers with sharp edges. Interestingly, the bandgap of the composites exhibited a blue shift (from 2.03 eV to 1.9 eV) with increasing concentrations of Zn _2 V _2 O _7 . The prepared samples were evaluated as photocatalysts for the degradation of Methylene Blue (MB) dye under natural sunlight. Among the composites, the sample with composition ${(V_{4}{O}_{7})}_{0.65}$ ${(V_{2}{O}_{5})}_{0.20}$ ${(Zn_{2}{V}_{2}{O}_{7})}_{0.15}$ demonstrated the highest degradation efficiency ( ∼ 95%), achieving complete degradation of MB dye after 45 minutes of natural solar irradiation, with a photodegradation rate constant of 0.06492 min ^−1 . This nearly threefold increase in efficiency compared to V _2 O _5 ( ∼ 28%) is primarily attributed to the enhanced charge separation efficiency within the composite structure.